The odds and implications of coinheritance of hemophilia A and B - Corinne Karch; Diane Masser‐Frye; Jacqueline Limjoco; Sarah E. Ryan; Shelley N. Fletcher; Kevin D. Corbett; Jill M. Johnsen; Courtney D. Thornburg (Research and Practice in Thrombosis and Haemostasis, 2020)
Abstract We report 2 patients with coinheritance of the X‐linked bleeding disorders hemophilia A and hemophilia B. We describe the family pedigrees, clinical features, and genotyping. The case report addresses the key clinical questions of how to manage patients with both hemophilia A and B and how to counsel families regarding recurrence risk. The patients with coinherited hemophilia A and B require a combination of factor VIII and factor IX replacement to achieve hemostasis. We calculated the estimated genomic meiotic recombination frequency between F8 and F9 to be 38%. The findings in these cases are consistent with this calculation. These findings provide critical information for management of families with coinherited hemophilia A and B.